KEY COMPONENTS STRATEGIC EFFECTIVENESS OF SUSTAINABLE DEVELOPMENT OF INDUSTRIAL ENTERPRISES - Svetlana Kalyugina; Hussein Laiq Hussein (Вестник Северо-Кавказского федерального университета, 2022)
In article are considered essential components of the concept of strategic effectiveness of sustainable development of industrial enterprise. Presented is a discussion of the effectiveness ratio, efficiency, sustainability, efficiency and effectiveness of strategic management. On the basis of various scientific perspectives offered author s interpretation of the definition of the strategic effectiveness of sustainable development, highlighted its components in relation to the industrial enterprises in the current economic conditions, which is the scientific novelty of the results of this study.